Equipment maintenance support capability evaluation using cloud barycenter evaluation method - Hongqiang Gu; Cheng Zhang; Quan Shi (Institute of Advanced Engineering and Science, 2013)
Maintenance support is the most important measures to keep equipments having high operational capabilities. Equipment maintenance support capability is an important part of operational capability and the evaluation of equipment maintenance support capability is very important to the establishment of battle effectiveness. The evaluation index system of equipment maintenance support capability is established according to the evaluation index establishing principles. Cloud barycenter evaluation method is applied to equipment maintenance support capability evaluation on basis of the established evaluation index system. The application steps of cloud barycenter evaluation method to equipment maintenance support capability evaluation are analyzed. A calculating example for equipment maintenance support capability using the proposed algorithm is presented and the evaluation results are achieved using the weighted deflection degree which is used to demonstrate the deflection degree between equipment maintenance support capability and its perfect state. The correctness and validity of the proposed method is verified by the calculating results, which provide an efficient method for equipment maintenance support capability evaluation. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.1982